Steep Posterior Tibial Slope and Excessive Anterior Tibial Translation Are Associated With Increased Sagittal Meniscal Extrusion After Posterior Lateral Meniscus Root Repair Combined With Anterior Cruciate Ligament Reconstruction - Zheng-Zheng Zhang, M.D., Ph.D; Hao-Zhi Zhang, M.D; Chuan Jiang, M.D., Ph.D; Rui Yang, M.D; Zhong Chen, M.D., Ph.D; Bin Song, M.D., Ph.D; Wei-Ping Li, M.D (Elsevier, 2024)
Purpose: To evaluate the clinical and radiographic outcomes of patients with primary anterior cruciate ligament reconstruction (ACLR) with type II posterior lateral meniscus root tear (PLMRT) repair and to identify whether increased anterior tibial subluxation of the lateral compartment (ATSLC) and steeper posterior tibial slope (PTS) are associated with sagittal lateral meniscal extrusion (LME). Methods: Patients who underwent primary anatomic ACLR with concomitant type II PLMRTs using the all-inside side-to-side repair technique between November 2014 and September 2020 were identified. To be included, patients must have had a minimum of 2 years follow-up. All patients, including those with ATSLC and PTS and sagittal and coronal LME, were retrospectively reviewed clinically and radiologically. The patients were divided into 2 subgroups according to the occurrence of sagittal LME. Results: Forty patients were included in this study with a mean follow-up of 44 months (range, 24-94 months). In general, the postoperative parameters, including grade of pivot shift, side-to-side difference, ATSLC, Lysholm score, and International Knee Documentation Committee (IKDC) score, were significantly improved compared with the preoperative ones. However, postoperative sagittal LME was detected to be significantly larger than the preoperative one. Minimal clinically important difference (MCID) analysis for postoperative outcomes showed that the rate of patients who achieved MCID thresholds was 100% for Lysholm, 95% for IKDC, 42.50% for coronal LME, 62.50% for sagittal LME, 40% for ATSLC, and 100% for side-to-side difference. Further comparisons, where patients were divided into 2 subgroups according to the occurrence of sagittal LME, showed significant differences in PTS, ATSLC, and coronal LME. Conclusions: Clinical outcomes after type II PLMRT repair with primary ACLR were significantly improved, except for LME, at the 2-year postoperative follow-up. After repair of type II PLMRT injuries, the presence of sagittal LME was associated with increased PTS and ATSLC. Level of Evidence: Level III, retrospective cohort study.